(3GdefgL , GdfXQjI , GdbjGSs - (3YUGe YeQ(B, (3efOhQs ((3GdGScfOQjI(B:s (3OGQ GdcJH GdeUQjI(B,s, 2011)
(3eaghe h fXQjGJ GdJfejI GdGbJUGOjI h GdJZjjQ GdJcfhdhLj aj GdOhd GdYQHjI , eaghe h eMOOGJ Gdgjcd GdGbJUGOj h eXGgQ GJZjjQ Gdgjcdj , GdSjGSI GdgjcdHI h fXQjGJ h eOGNd bjGS GdJZjjQ Gdgjcdj , bjGS GdYdGbI GdeJHGOdI Hjf GdJZjjQ Gdgjcdj h YedjI GdJfejI GdGLJeGYjI h GdGbJUGOjI aj GdOhd GdYQHjI h eUQ h JMdjd GJLGYGJ GdJZjjQ Gdgjcdj aj GdfTGW GdGbJUGOj GdeUQj , h CNjQG bjGS gPG GdJajjQ h JMOjO CSHGHgs
(3eQGLY U(B.307 (3; edMb GMUGFj U(B.325 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdJfejIs; (3GdJfejI GdEbJUGOjI hGdGLJeGYjIs; (3GdJfejI(B- (3GdhWf GdYQHjs